2023
DOI: 10.3390/nu15143102
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Mental Health among Venezuelan Migrants and Refugees Living in Peru: Secondary Data Analysis of a Cross-Sectional Survey

Abstract: The objective of this study was to analyze the association between food insecurity and mental health in Venezuelan migrants and refugees residing in Peru using data from the Survey Directed at the Venezuelan Population Residing in the Country (ENPOVE) conducted in 2022. The analysis included 7739 Venezuelan adults. The presence of mental health problems was self-reported, and household food insecurity was measured using the Food Insecurity Experience Scale. The study found that 4 out of 10 participants lived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…There appeared to be a dose-response relationship in which membership in Class 2 (high material hardships and food insecurity) had the lowest odds of good to excellent self-rated health and had the highest odds of anxiety or depressive symptomatology, as well as recent violence victimization. These findings are consistent with global research that has demonstrated the direct links between food insecurity and material hardships with mental health, as well as indirect relationships with mental and physical health through malnutrition and delayed medical care [34][35][36]. Similarly, household food insecurity and material hardships have been associated with increased household stress that may trigger violent behavior, while survivors experiencing food insecurity and material hardships may not have the means to access safer housing or to escape abusive relationships, thus increasing the risk of violence victimization [37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…There appeared to be a dose-response relationship in which membership in Class 2 (high material hardships and food insecurity) had the lowest odds of good to excellent self-rated health and had the highest odds of anxiety or depressive symptomatology, as well as recent violence victimization. These findings are consistent with global research that has demonstrated the direct links between food insecurity and material hardships with mental health, as well as indirect relationships with mental and physical health through malnutrition and delayed medical care [34][35][36]. Similarly, household food insecurity and material hardships have been associated with increased household stress that may trigger violent behavior, while survivors experiencing food insecurity and material hardships may not have the means to access safer housing or to escape abusive relationships, thus increasing the risk of violence victimization [37][38][39].…”
Section: Discussionsupporting
confidence: 90%